2014
DOI: 10.1063/1.4871500
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of model Kohn–Sham potentials for orbital-dependent functionals: A practical alternative to the optimized effective potential method

Abstract: We describe a method for constructing a hierarchy of model potentials approximating the functional derivative of a given orbital-dependent exchange-correlation functional with respect to electron density. Each model is derived by assuming a particular relationship between the self-consistent solutions of Kohn-Sham (KS) and generalized Kohn-Sham (GKS) equations for the same functional. In the KS scheme, the functional is differentiated with respect to density, in the GKS scheme--with respect to orbitals. The lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 92 publications
(103 reference statements)
2
50
0
Order By: Relevance
“…Moreover, we mention the work of Staroverov and coworkers 83,107 who proposed an expression for a multiplicative exchange potential (making no use of unoccupied orbitals) which leads to results that are quasiidentical to the EXX-OEP results. However, this approach requires the HF orbitals which reduces its use for solids and large scale applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we mention the work of Staroverov and coworkers 83,107 who proposed an expression for a multiplicative exchange potential (making no use of unoccupied orbitals) which leads to results that are quasiidentical to the EXX-OEP results. However, this approach requires the HF orbitals which reduces its use for solids and large scale applications.…”
Section: Discussionmentioning
confidence: 99%
“…83 for a summary of the expression of these potentials). These nonlocal potentials avoid some of the technical difficulties of EXX-OEP as their construction involves only the occupied orbitals.…”
Section: Discussionmentioning
confidence: 99%
“…RKS-type potentials generated from HF wave functions are known to be excellent approximations to exchange-only optimized effective potentials. 8,9 The message of this figure is that molecular exchangecorrelation potentials of high quality can be effortlessly generated by the mRKS method.…”
Section: Comparison Of the Original And Modified Rks Methodsmentioning
confidence: 99%
“…As a quality control test, |∆E vir | is more discriminating than ∆ ρ : even visually imperceptible defects of v XC (r) can result in large ∆E vir values, as we showed previously for approximate exchange-only potentials. 8,9,49,50 Note that in Refs. 8 and 9 we studied KS potentials extracted from HF wave functions as approximations to exact-exchange potentials, for which T c = 0, so we defined ∆E vir = W − E HF X and evaluated E HF X using the KS (not HF) orbitals.…”
Section: Comparison Of the Original And Modified Rks Methodsmentioning
confidence: 99%
“…23 and 24 for MGGAs). However, comparisons between the EXX-OEP and the KLI approximation (EXX-KLI in the following) concern mainly atoms and light molecules/clusters 8,[15][16][17][34][35][36][37][38][39][40][41][42][43][44] and only a few such comparisons were done for periodic systems. 8,11,45,46 From most of these studies, it was concluded that EXX-KLI is a good approximation to EXX-OEP, however, in Refs.…”
Section: 5mentioning
confidence: 99%